VD_FINDINFO AA 91/09 - 53/2011 vom 2. Mai 2011 - VD Tribunal cantonal (2011)
ACCIDENT, DROIT À LA PRESTATION D'ASSURANCE, LIEN DE CAUSALITÉ, LÉSION CORPORELLE ASSIMILÉE À UN ACCIDENT | 6 LAA, 4 LPGA, 9 OLAA